Interferon-gamma in patients with alopecia universalis - Emina Kasumagic-Halilovic (Our Dermatology Online, 2018)
Background: Alopecia universalis (AU) is an uncommon form of alopecia areata that involves the loss of all hear and body hair. The cause of AU is unknown, although most evidence supports the hypothesis that AU is a T-cell mediated autoimmune disease of the hair follicle and that cytokines play an important role. Objective: The aim of our study was to evaluate serum concentrations of interferon-g (IFN-g) in patients with AU and healthy subjects and also to asses a possible association between IFN-g and duration of the disease. Material and Methods: Twenty two patients with AU and 20 healthy controls were enrolled in the study. Serum concentrations of IFN-g were measured using enzyme-linked immunoassay techniques. Results: The serum concentration of IFN-g in patients with AU was significantly higher than that in the control group (12.050 pg/ml vs 10.000 pg/ml, respectively; p < 0.0001). No correlations were found between duration of disease and the serum levels of IFN-g (p= 0.3048). Conclusion: Our results have demonstrated the importance of determining IFN-g concentrations in serum in patients with AU. This research could contribute to the interpretation of insufficiently well known views of the pathogenesis role and significance of IFN-g in AU.